1983
DOI: 10.3109/03639048309039889
|View full text |Cite
|
Sign up to set email alerts
|

Xilobam: Effect of salt form on pharmaceutical properties

Abstract: In an e f f o r t t o p r o t e c t xilobam from t h e e f f e c t s of h i g h temperatures and h i g h h u m i d i t i e s w i t h o u t a d v e r s e l y a f f e c t i n g i t s d i s s o l u t i o n from t a b l e t s , t h r e e a r y l s u l f o n i c a c i d s a l t s and t h e s a c c h a r i n s a l t were p r e p a r e d . A l l o f t h e s a l t s were determined t o be more s t a b l e a t 74% r e l a t i v e humidity and 70' t h a n t h e f r e e b a s e .I n s p i t e of t h e l a r g e d i f f e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In fact, it has been found that the presence of aryl groups in the sulfate counterion for this drug protected the base from getting easily hydrolyzed in the presence of high humidity and high temperatures. The formation of hydrophobic salts allows pharmaceutical companies to prepare more stable drugs without affecting their bioavailability [ 16 ]. Salt formation leads to increased lipophilicity as a result of the neutralization of the overall electrostatic charge, thereby enhancing the membrane permeability of hydrophilic molecules.…”
Section: Drug Chemistry Considerationsmentioning
confidence: 99%
“…In fact, it has been found that the presence of aryl groups in the sulfate counterion for this drug protected the base from getting easily hydrolyzed in the presence of high humidity and high temperatures. The formation of hydrophobic salts allows pharmaceutical companies to prepare more stable drugs without affecting their bioavailability [ 16 ]. Salt formation leads to increased lipophilicity as a result of the neutralization of the overall electrostatic charge, thereby enhancing the membrane permeability of hydrophilic molecules.…”
Section: Drug Chemistry Considerationsmentioning
confidence: 99%
“…The immediate environment of the drug in a formulation can influence salt to free acid/base conversions thereby causing instability or affecting product performance (14,15). Often, the free acid/base forms of drugs are inherently unstable and hence salt forms have to be used in formulations (1,16). Minimizing exposure to water during processing and the use of an alkalinizer minimized the conversion of a stable salt to an unstable free acid, thereby improving stability during the process and storage (1).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical degradation of API commonly defines the shelf life of a drug product. It has been shown that different polymorphs or salts of an API have different chemical stability [77,78]. The crystal structure of the API may be important in chemical stability.…”
Section: The Role Of Api Properties Solid Form and Particle Engineermentioning
confidence: 99%
“…It has been shown that different polymorphs or salts of an API have different chemical stability. [77,78] The crystal structure of the API may be important in chemical stability. On rare occasions, the structure of the API may leave it prone to degradation through the location of the reactive groups in the crystal structure; this is referred to as topochemistry.…”
Section: Shelf Life (Stability)mentioning
confidence: 99%